1971
DOI: 10.1083/jcb.51.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Phosphorylation and Ultrastructural Transformation in Mitochondria in the Intact Ascites Tumor Cell

Abstract: We have examined the ultrastructure of mitochondria as it relates to energy metabolism in the intact cell . Oxidative phosphorylation was induced in ultrastructurally intact Ehrlich ascites tumor cells by rapidly generating intracellular adenosine diphosphate from endogenous adenosine triphosphate by the addition of 2-deoxyglucose . The occurrence of oxidative phosphorylation was ascertained indirectly by continuous and synchronous monitoring of respiratory rate, fluorescence of pyridine nucleotide, and 90° li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1
2

Year Published

1974
1974
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(76 citation statements)
references
References 18 publications
3
70
1
2
Order By: Relevance
“…33,34 In the apoptotic cells we found two subsets of mitochondria, and in addition the respiring mitochondria display now the conformation related to increased ATP generation. Hackenbrock called this the`condensed conformation', but also stresses that a more specific sign of stimulated mitochondria is the intracristal dilatation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…33,34 In the apoptotic cells we found two subsets of mitochondria, and in addition the respiring mitochondria display now the conformation related to increased ATP generation. Hackenbrock called this the`condensed conformation', but also stresses that a more specific sign of stimulated mitochondria is the intracristal dilatation.…”
Section: Discussionmentioning
confidence: 96%
“…Hackenbrock called this the`condensed conformation', but also stresses that a more specific sign of stimulated mitochondria is the intracristal dilatation. 34 In fact a previous study on etoposide treated THP.1 cells showed intracristal dilatation in the`ultracondensed' mitochondria. 17 Moreover, besides the altered mitochondria, these authors reported casually the persistence of mitochondria with normal ultrastructural configuration.…”
Section: Discussionmentioning
confidence: 99%
“…The signi®cance of this mitochondrial morphological transformation remains to be elucidated. However, condensed mitochondria have been associated with higher oxidative phosphorylation e ciency (De Martino et al, 1979;Hackenbrock et al, 1971). Therefore, it is possible that mitochondrial transformation might be a cellular mechanism to compensate for decreased oxygen supply to cells in the adluminal compartment due to the blood-testis barrier (Waites and Gladwell, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo mitochondrial contractions were obtained by treating 1-mm thick sections of corn shoots with 2.5 mM 2DOG2 for 20 min (11). The sections were then fixed in 2% glutaraldehyde in 0.2 M cacodylate buffer.…”
Section: Methodsmentioning
confidence: 99%